Curriculum-based sexual and reproductive health education: revealing its relevance for risky sexual behaviors among secondary school students in Mwanza, Tanzania - Ng'wamba Sitta Ngissa; Erica Sanga; Mussa Kelvin Nsanya; Belinda Kweka; Evangelista Malindisa; Rosemarie Mwaipopo (BMC, 2024)
Abstract Background Secondary school students are vulnerable to risky sexual behaviors (RSBs) which may lead to adverse health consequences, such as teenage pregnancies and sexually transmitted diseases (STDs), including HIV/AIDS. In Tanzania, the burden of teenage pregnancy was reported to be 27% in 2016. The integration of sexual and reproductive health (SRH) education into the school curriculum is one of the proven crucial interventions. However, there is limited information on the extent to which curriculum-based SRH education is relevant for fostering good practices for coping with RSBs. This study sought to describe students' and teachers' perceptions of the relevance of curriculum-based SRH education. Methods A qualitative study was conducted from May to June 2020 (involving 5 secondary schools in Ilemela district, Mwanza, Tanzania). In-depth interviews (30) were conducted among secondary school students and 10 interviews for teachers. The data were collected in Swahili and then transcribed and translated into English after which thematic content analysis was performed. Results The majority (56%) of secondary school students were revealed to have a limited understanding of curriculum-based SRH education, which was limited to a few aspects of health that involved married people and pregnant women. Teachers of different subjects had different perceptions about the relevance of curriculum-based SRH education. Civics teachers had the perception that it was relevant and enough, while Biology teachers thought that it was not enough. Students reported utilizing the information taught in class to manage and navigate RSBs. Moreover, they expressed a need for additional delivery strategies to be used for a comprehensive understanding of sexual and reproductive health. Conclusion Despite the identified gaps in providing a comprehensive knowledge that builds on the appropriate attitudes and skills, the existing curriculum-based SRH education in secondary schools was utilized to help students in addressing and managing RSBs. However, there is a need for more comprehensive information and an improved delivery approach for SRH to equip students with the necessary skills when faced with RSBs.